Strategic Planning Madrasah Pembangunan Ciputat - Dian Nuraini; Suryadi Suryadi; Siti Zulaikha (STAI Miftahul Ula Nganjuk, 2020)
This study aims to obtain a complete picture of strategic planning in Madrasah Pembangunan. How can the mandate, vision, and mission of the organization be outlined in strategic planning as a reference and guide in carrying out programs and activities? The research instrument is a researcher who is also known as a human instrument. Determination of informants by purposive sampling. The technique of collecting data is direct observation, photographing the research site, recording interviews with resource persons, and collecting data or documents obtained from resource persons. Findings from the research (1) Strategic planning has been implemented properly and has become a quality assurance system as outlined in the quality policy and quality objectives in each unit in the Madrasah Pembangunan as a reference for every policy in management. The 2018 Madrasah Pembangunan Blueprint is a planning document that has a vision that is in line with current trends and can be applied to accommodate developments in the world of education that lead to technological advances and global information flows.